Phosphite treatment can improve root biomass and nutrition use efficiency in wheat - Mohammed, Umar; Davis, Jayne; Rossall, Steve; Swarup, Kamal; Czyzewicz, Nathan; Bhosale, Rahul; Foulkes, John; Murchie, Erik H.; Swarup, Ranjan (Frontiers in Plant Science, 2022)
Phosphite represents a reduced form of phosphate that belongs to a class of crop growth- promoting chemicals termed biostimulants. Previous research has shown that phosphite application can enhance root growth, but its underlying mechanism, especially during environmental stresses, remains elusive. To uncover this, we undertook a series of morphological and physiological analyses under nutrient, water and heat stresses following a foliar application in wheat. Non-invasive 3D imaging of root system architecture directly in soil using X-ray Computed Tomography revealed that phosphite treatment improves root architectural traits and increased root biomass. Biochemical and physiological assays identified that phosphite treatment significantly increases Nitrate Reductase (NR) activity, leaf photosynthesis and stomatal conductance, suggesting improved Nitrogen and Carbon assimilation, respectively. These differences were more pronounced under heat or drought treatment (photosynthesis and photosystem II stability) and nutrient deficiency (root traits and NR). Overall our results suggest that phosphite treatment improves the ability of plants to tolerate abiotic stresses through improved Nitrogen and Carbon assimilation, combined with improved root growth which may improve biomass and yield.